NEW DISTRIBUTION RECORDS OF SUNDA COUCAL Centropus nigrorufus FOR BALI AND MADURA ISLAND, INDONESIA - Prihatmoko, Oka Dwi; Nugroho, Husnaeni; Nuarta, Putu Wiwin; Salehah, Fitriana (Masyarakat Zoologi Indonesia, 2023)
Sunda Coucal is known to be endemic to Java Island. This report documented the sightings of Sunda Coucal Centropus nigrorufus on Bali and Madura, Indonesia. There are 7 sightings within three different areas in Bali and six different areas in Madura. These records are to be new records of Sunda Coucal which widen its distribution outside mainland of Java Island. Based on the presence of this bird in the bird market, the distance of Java and Bali or Java and Madura are very close, and no information from previous records of this species in Madura and Bali. It is presumed that this species could be a feral bird rather than an overlooked species in the past.